Architectural acoustics : principles and practice - Cavanaugh, William J.; Tocci, Gregory C.; Wilkes, Joseph A. (Hoboken, N.J. : John Wiley & Sons, 2010)
'A widely recognized, comprehensive reference to acoustic principles for all concerned with the built environment, Architectural Acoustics, Second Edition provides design professionals with up-to-date information on basic concepts, acoustical materials, and technologies for controlling wanted or unwanted sound within and around buildings.''Written by a team of internationally recognized experts and experienced consultants, this Second Edition covers fundamental acoustic principles, design criteria, acoustical materials, control strategies, and methods for a wide variety of building types, including educational, healthcare, recreational, residential, commercial, industrial, and transportation facilities. Particular attention is given to places for listening and performance such as theaters, churches, concert and recital halls, outdoor arenas, classrooms, multiuse auditoria, libraries, music practice and rehearsal rooms, recording and broadcast studios, sports venues, home theaters, and other spaces that people meet to communicate and enjoy performance.'--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Architectural acoustics